2008
DOI: 10.1515/hf.2008.073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on structural performance of compressed wood as shear dowel

Abstract: This study addresses the application of compressed wood (CW) made of Japanese cedar, as a substitute for high-density hardwood, to shear dowel. A double woodto-wood shear test was performed to evaluate the mechanical shear properties of CW perpendicular to the grain, and the results were compared with those of several types of dowel material. CW with its annual ring radial to loading direction (08) had a unique double shear performance characteristic, and showed good properties as a dowel material by virtue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…For example, Seborg et al (1945) reported about compressed wood with the commercial name Staypak. Compression or densification of wood is still a topic of interest (Jung et al 2008;Kamke and Rathi 2011;Laine et al 2013) also in the context of resistance of wood products against fungi (Skyba et al 2008(Skyba et al , 2009. Densification leads to plastic deformation of wood as a whole and its cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Seborg et al (1945) reported about compressed wood with the commercial name Staypak. Compression or densification of wood is still a topic of interest (Jung et al 2008;Kamke and Rathi 2011;Laine et al 2013) also in the context of resistance of wood products against fungi (Skyba et al 2008(Skyba et al , 2009. Densification leads to plastic deformation of wood as a whole and its cells.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of the presented joints are as follows: (i) an easy joint assembly that can be automated by computer-controlled systems, (ii) an initial degree of freedom of rotation for achieving final assembly after joining the wood parts and for correcting assembly tolerances (e.g. for wooden truss structures), (iii) a long-term rigidity by achieving form-and-friction locking due to high and reliable swelling pressures, (iv) a generic higher ductility at failure load compared to native hardwood dowels, given a dowel failure (Jung et al 2008) and (v) use of the highly abundant beech wood. Disadvantages can be seen in the more complex production process including a densification step and a CNC milling step, and in the fact that the beech dowels do not permit applications under outdoor conditions because of the low durability.…”
Section: Double Shear Lap Joint Tests With Cylindrical Dovetailed Dowelsmentioning
confidence: 99%
“…Research on dW often focuses on permanent fixation of the densified state based on methods of chemical or thermal treatment before, during or after densification (Morsing and Hoffmeyer 1998;Navi and Girardet 2000;Wolcott and Shutler 2003;Blomberg 2006;Kutnar et al 2008;Skyba 2008;Laine 2014;Palma et al 2016). In contrast, shape recovery is beneficial in the case of dW as a structural swelling component (Jung et al 2008;Guan et al 2010). However, the mechanical behavior of dW as a swelling dowel has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behaviour of welded dowels was obtained by shearing tests showing rapidly yield considerable strength for welded wood dowel assemblies. Guan et al [6] and Jung et al [10] have studied timber joint systems using compressed wood fasteners and plates in place of steel fasteners. Tests have been made on different types of beam-to-column connections.…”
Section: Introductionmentioning
confidence: 99%